2001
DOI: 10.1046/j.1570-7458.2001.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in damage to cotton affecting larval feeding preference of Spodoptera littoralis

Abstract: Feeding experiments with larvae of Spodoptera littoralis were performed with leaves from cotton plants subjected to damage and from undamaged plants. In the experiments, four different time intervals (1, 3, 7, and 14 days) after damage induction and two different levels (high and low) of herbivore damage were tested. Seven days after damage induction larvae fed less on the young top leaves from damaged plants for both levels of damage. At the high damage level, the larvae fed less on leaves from the damaged pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 22 publications
6
28
1
Order By: Relevance
“…Under our study conditions, no response was observed after damages involving a small number of caterpillars or attacks of short duration. Similar findings have been reported in cotton Gossypium hirsutum in which the induced response to attack by Spodoptera littoralis depends on the extent of damage (Anderson et al, 2001). In Brassica napus, the increase in concentration of glucobrassicine (but not the other 13 glucosinolates analyzed) depends on the intensity of the damage inflicted by Delia floralis larvae (Hopkins et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Under our study conditions, no response was observed after damages involving a small number of caterpillars or attacks of short duration. Similar findings have been reported in cotton Gossypium hirsutum in which the induced response to attack by Spodoptera littoralis depends on the extent of damage (Anderson et al, 2001). In Brassica napus, the increase in concentration of glucobrassicine (but not the other 13 glucosinolates analyzed) depends on the intensity of the damage inflicted by Delia floralis larvae (Hopkins et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings have been observed in tobacco in which the peak increase of nicotine production occurs 7Y8 d after the beginning of the attack (Baldwin, 1989). In cotton, attack by S. littoralis induces a strong response 5Y10 d after the beginning of the attack but not after only 1Y3 d (Anderson and Alborn, 1999;Anderson et al, 2001). Previously attacked leeks may present higher precursor levels than neverattacked plants for a long time after injury.…”
Section: Discussionsupporting
confidence: 76%
“…The strength of induced resistance decreased gradually with time in our system, which corroborates earlier studies on non-clonal plants (Stout et al 1996;Anderson et al 2001;Agrell et al 2003;Alves et al 2007). One of the four genotypes used in this study, however, showed a prolonged strong decrease in palatability after defense induction, indicating differences in defense timing between the selected genotypes in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Host plant location and acceptance behaviors toward damaged plants are partially decoupled in other lepidopterans. Studies on related noctuid caterpillars in other plants indicate that larvae tend to move away from herbivore-damaged or induced plant tissues, if they move at all on the plant (McAuslane and Alborn, 2000; Anderson et al, 2001). Female Trichoplusia ni moths orient toward herbivore-damaged rather than undamaged plants, but preferentially oviposit on undamaged plants when given a choice (Landolt, 1993(Landolt, , 2001.…”
Section: Discussionmentioning
confidence: 99%